1993
DOI: 10.1111/j.1365-2141.1993.tb03353.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different human immunodeficiency virus type‐1 (HIV‐1) isolates on long‐term bone marrow haemopoiesis

Abstract: Summary. Haemopoietic cytopenias are a frequent occurrence in human immunodeficiency virus type‐1 (HIV‐1) induced disease. In order to examine the possible direct inhibition of marrow haemopoiesis by HIV‐1, we have investigated the effect of HIV‐1 infection on myelopoiesis in long‐term bone marrow cultures. In vitro exposure of normal marrow cultures to three different lymphocytotropic HIV‐1 isolates resulted in productive infection, as demonstrated by a progressive increase of gag p24 antigen. In these exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Most studies indicate that bone marrow-derived HSCs cannot be infected by HIV-1 until they undergo modest differentiation in order to express the appropriate receptors to enable virus entry and subsequent replication [59]. Studies have demonstrated the presence of both CD4 [94] and the chemokine receptors CXCR4 and CCR5 [95] on CD34 [62,81]. The natural chemokine ligands for the major HIV-1 coreceptors are able to readily block entry of HIV-1 [96].…”
Section: Direct Infection Of Cd34mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies indicate that bone marrow-derived HSCs cannot be infected by HIV-1 until they undergo modest differentiation in order to express the appropriate receptors to enable virus entry and subsequent replication [59]. Studies have demonstrated the presence of both CD4 [94] and the chemokine receptors CXCR4 and CCR5 [95] on CD34 [62,81]. The natural chemokine ligands for the major HIV-1 coreceptors are able to readily block entry of HIV-1 [96].…”
Section: Direct Infection Of Cd34mentioning
confidence: 99%
“…HIV-1-infected patients suffer from many hematologic disorders and exhibit uni or multilineage suppression of bone marrow hematopoiesis including anemia, lymphocytopenia, thrombocytopenia, granulocytopenia, monocytopenia, and neutropenia that can be attributed to malfunction or premature death of the specific hematopoietic cells [8, [57][58][59]. The hematopoietic disorders are frequently associated with impaired HPC growth, BM dysplasia, plasmacytosis, and lymphoid infiltrates [57,60], and they suggest virusinduced abnormalities in the bone marrow microenvironment [61][62][63]. T cell depletion in AIDS is thought to be, at least in part, due to the failure of T cell development from lymphohematopoietic stem cells [14].…”
Section: Bone Marrow Hematopoiesis Disorders Associated With Hiv-1 Inmentioning
confidence: 99%